Financial integration in Europe through the lens of composite indicators - Peter Hoffmann; Manfred Kremer; Sonia Zaharia (European Central Bank (ECB), 2019)
This paper develops composite indicators of financial integration within the euro area for both price-based and quantity-based indicators covering money, bond, equity and banking markets. Prior to aggregation, individual integration indicators are harmonised by applying the probability integral transform. We find that financial integration in Europe increased steadily between 1995 and 2007. The subprime mortgage crisis marked a turning point, bringing about a marked drop in both composite indicators. This fragmentation trend reversed when the European banking union and the ECB's Outright Monetary Transactions Programme were announced in 2012, with financial integration recovering more strongly when measured by pricebased indicators. In a growth regression framework, we find that higher financial integration tends to be associated with an increase in per capita real GDP growth in euro area countries. This correlation is found to be stronger the higher a country's growth opportunities.
Keywords: F36; F43; F45; G01; G15; 330; composite indicator; economic growth; European Monetary Union; financial integration; financial stress